Finite Element Analysis to Investigate the Effects of Split Sleeve Cold Expansion Process Variables on Residual Stress Distribution and Pulling Force Progression for Al 2024-T351 Alloy - Md. Saddam Hossen; Luis Brito Santana; Hua Tan; Dave Kim (International Journal of Aerospace Engineering)
The split sleeve cold expansion process is broadly utilized in aerospace metallic structures to improve the fatigue life of fastener holes. However, the effectiveness of this process is highly affected by variations in key process parameters. This numerical parametric study investigates the effect of hole size variations up to 0.09 mm, frictional coefficient up to 0.1, and mandrel pulling angle up to 1.5° on the outcomes of the split sleeve cold expansion process for a 7.59-mm hole in aluminum 2024-T351. This study primarily focuses on two primary outcomes: residual stress fields and the evolution of pulling force. Explicit 3D FE models were developed using ABAQUS 6.19 to simulate the process. The results of this investigation indicate that geometric variations in hole diameter lead to a reduced magnitude of peak compressive residual stress and a smaller compression region at the hole’s entrance face by up to 24% when compared to the straight hole. When the mandrel’s pulling angle is 1.5°, the distribution of compressive residual stresses becomes asymmetrically around the hole, with a declining trend in circumferential compressive stress magnitude at the entry and exit faces near the hole. Additionally, an increase in the coefficient of friction from 0.05 to 0.1 results in an increase of the maximum pulling forces by 62%–74%; however, its impact on the circumferential residual stresses is minimal.